2003
DOI: 10.1021/jp022267l
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Dilute Clusters of Methane and Water by ab Initio Quantum Mechanical Calculations

Abstract: Ab initio quantum mechanical methods have been used to examine clusters formed of molecules of methane and water. The clusters contained one molecule of one component (methane or water) and several (10, 8, 6, 4, and 1) molecules of the other component. The Møller−Plesset perturbation theory (MP2 method) was used in the calculations. The cluster geometries were obtained via optimization and the interaction energies between the nearest neighbors were calculated for the geometries obtained in the first step. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 72 publications
3
27
0
Order By: Relevance
“…In the classical theory of solutions, a hydrophobic solute molecule becomes encapsulated in a hydration cell (i.e., cavity) formed of water molecules. The hydration cell around the hydrophobic solute requires both restructuring and some loss of hydrogen bonding on the water molecules' part (see Ruckenstein et al 2003 and references therein). As water molecules are mobile, particularly in the liquid phase, forming a hydration cell demands that a solute molecule enter immediately or the cell will collapse.…”
Section: Appendix a Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation
“…In the classical theory of solutions, a hydrophobic solute molecule becomes encapsulated in a hydration cell (i.e., cavity) formed of water molecules. The hydration cell around the hydrophobic solute requires both restructuring and some loss of hydrogen bonding on the water molecules' part (see Ruckenstein et al 2003 and references therein). As water molecules are mobile, particularly in the liquid phase, forming a hydration cell demands that a solute molecule enter immediately or the cell will collapse.…”
Section: Appendix a Nomenclaturementioning
confidence: 99%
“…We take Z = 20 (Jorgensen et al 1985). For the spherical cavity radius, we assume a cavity = 3.74 × 10 −8 cm based on the carbon-oxygen distance found via molecular cluster simulations (Ruckenstein et al 2003). The cavity radius is also adjusted to pressure using the multiplication factor of Equation (C11).…”
Section: Appendix a Nomenclaturementioning
confidence: 99%
“…The structure of the solid hydrate and different methane-water clusters was also subject of extensive theoretical [4][5][6][7][8][9][10][11], and spectroscopic studies [12][13][14][15][16][17][18][19]. A main concern for the computational studies was to create a proper potential for molecular dynamics calculations [4,5,7,8], and to determine the hydratation number of methane. Monte Carlo simulations revealed that a distorted dodecahedral structure has a high statistic probability; furthermore it was shown that the interaction between solvent molecules around the methane is stronger than that in the bulk liquid [4].…”
Section: Introductionmentioning
confidence: 99%
“…While the interaction energy at the HF/6-31+G ** level was somewhat more than 2 kcal/mol, using a composite scheme [11] to extrapolate for larger basis sets and electron correlation (MP2) the interaction energy increases above 5 kcal/mol. In a recent MP2/6-31+G ** ab initio study, a single dodecahedral cage occupied with methane was investigated [7]. It has been concluded that the insertion of a methane molecule in this cage results in minor structural changes of the water network.…”
Section: Introductionmentioning
confidence: 99%
“…The basis set that includes both diffuse and polarization functions has already been used for several hydrogen bonded systems. [42][43][44][45][46][47][48] The energies are corrected for BSSE using counterpoise method and generalized counterpoise method. [49][50][51] …”
Section: Computational Detailsmentioning
confidence: 99%